Clinical observation and evaluation of health management intervention in controlling senile chronic diseases such as hyperlipidemia - Hongxia Liu (SLAS Technology, 2025)
Irregular diet, lack of exercise, and poor sleep quality have led to various diseases, with chronic conditions like hyperlipidemia being most common among the elderly. With advances in the medical Internet of Things (MIoT), medical data now supports more effective care strategies. Health management intervention, as a novel approach, aims to improve elderly patients’ understanding and management of chronic diseases. In this study, 200 elderly patients with hyperlipidemia were randomly divided into a control group (routine care) and an experimental group (health management intervention). Results showed that health knowledge mastery improved significantly with intervention—rising from 61.8 % to 74.4 % in males and from 56.8 % to 71.6 % in females. Thus, health management intervention based on medical data effectively enhances patients’ health literacy.